Effects of the 5′‐Triphosphate Metabolites of Ribavirin, Sofosbuvir, Vidarabine, and Molnupiravir on CTP Synthase Catalysis and Filament Formation: Implications for Repurposing Antiviral Agents against SARS‐CoV‐2. (26th October 2022) - Gillis, Thomas D.; Bearne, Stephen L.
Abstract: Repurposing of antiviral drugs affords a rapid and effective strategy to develop therapies to counter pandemics such as COVID‐19. SARS‐CoV‐2 replication is closely linked to the metabolism of cytosine‐containing nucleotides, especially cytidine‐5′‐triphosphate (CTP), such that the integrity of the viral genome is highly sensitive to intracellular CTP levels. CTP synthase (CTPS) catalyzes the rate‐limiting step for the de novo biosynthesis of CTP. Hence, it is of interest to know the effects of the 5′‐triphosphate (TP) metabolites of repurposed antiviral agents on CTPS activity. Using E. coli CTPS as a model enzyme, we show that ribavirin‐5′‐TP is a weak allosteric activator of CTPS, while sofosbuvir‐5′‐TP and adenine−arabinofuranoside‐5′‐TP are both substrates. β‐d ‐ N 4 ‐Hydroxycytidine‐5′‐TP is a weak competitive inhibitor relative to CTP, but induces filament formation by CTPS. Alternatively, sofosbuvir‐5′‐TP prevented CTP‐induced filament formation. These results reveal the underlying potential for repurposed antivirals to affect the activity of a critical pyrimidine nucleotide biosynthetic enzyme. Abstract : The repurposing of antiviral drugs may afford therapies to counter pandemics such as COVID‐19. Viral replication is sensitive to intracellular CTP levels, yet little is known about the effects of antiviral drug metabolites on CTP synthase activity. We show that the 5′‐triphosphates of several antiviral drugs can act as substrates, activators, or inhibitors of the enzyme, underscoring the need to explore such effects.